Goldilocks and the three “Ts”: targeting, testing, and tracking for “just right” democratic policing - Sherman, Lawrence W. (Criminology & public policy, 2022)
Police are often criticized for doing “too much” or “too little” policing in various situations. These criticisms amount to testable hypotheses about whether “less” force, or intensity, or enforcement would have been enough, or whether “more” was needed. The rise of evidence-based policing provides a starting point for public dialogues about those hypotheses, in ways that could help to build police legitimacy. Such dialogues can be focused on the questions posed by the three “Ts”: (1) Is police action targeted in a way that is proportionate to the harm that it can prevent? (2) Has the action been tested and found effective with the kinds of targets, and their levels of harm, where it is being used? (3) Is police action tracked to ensure it is delivered in the way that has been tested, and in compliance with relevant legal requirements? In this lecture, I frame the issue as follows: Can more widespread use of better research evidence on targeting, testing, and tracking police actions, shared more clearly among the public and police, help reduce the wide range of oscillation between over-policing and under-policing?